Ecotoxicological Assessment of Leachate from Municipal Solid Waste Dumpsites - C. N Angaye Tariwari; I. Seiyaboh Enetimi (Journal of Experimental and Clinical Toxicology, 2019)
The ecotoxicological effects of leachates from dumpsite have become a major problem. Leachates arising from waste dumpsites are transported by surface runoff or infiltration through the soil and become bioavailable in the ecosystem. The ecotoxicological assessment of leachates from 6 dumpsite in Yenagoa Metropolis were investigated against adult and fingerlings of Clarias gariepinus (African catfish). Ecotoxicological activities (LC50 values) were reported for the following stations; Akenpai (124.57 ppm), and Etegwe stations (95.38 ppm), as well as Opolo (157.95 ppm), and Kpansia Markets (123.82 ppm). In addition, leachates of the two stations from the central dumpsite (CDS), were the most active (CDS 1; 60.97 ppm, and CDS 2; 76.65 ppm). Notwithstanding, the order of toxicological activities of the leachates were reported as; CDS 1>CDS2>Etegwe>Akenpai>Kpansia market>Opolo Market. These results confirm the toxicity of leachates from the dumpsites. In addition, we recommend that government, regulators and all stakeholders should enact policies to treat, reduce, recycle and reduce waste stream in order to mitigate the adverse effects on the ecosystem.
Keywords: Ecotoxicity